Bacterial contamination and associated factors among food handlers working in the cafeterias at Tripoli University - Asma Mesbah Elkammoshi; Aya Muktar Abdulatif; Hiba Hendi Alsnosi Alsharif; Muna Elkouha; Hanan Jummah Duwahiyah; Heba Meloud Abuhelala (African Journal of Advanced Pure and Applied Sciences, 2024)
The research aims to assess the rate of bacterial contamination of surfaces, equipment, and hands that encounter food while being prepared in a university cafeteria. A cross-sectional study was conducted from May 2022 to July 2022 among food handlers working in the student cafeterias of Tripoli University’s main campus. A total of 100 samples were collected over a two-month period and the isolates were identified using morphological appearance on both selective and differential media as well as biochemical tests before antibiotic sensitivity test was done. Out of the 100 samples, 92 (92%) were positive for different bacterial species and 8 (8%) samples showed no growth of any bacteria. Also, among the positive isolates, gram-negative bacteria prevalence was the highest with 61 (58%), while gram-positive bacteria were 35 (38%). The gram-negative bacteria identified were E. coli 22 (24%), Klebsiella 20 (21%), P. aeruginosa 15 (16%) and Proteus 1 (1%), while the gram-positive bacteria was S. aureus 35 (38%). S. aureus and P. aeruginosa showed resistance to colistin and ceftriaxone while the other bacteria were susceptible to the antibiotics tested. This study observed that the level of hygiene among the food handlers in restaurants at Tripoli University was unsatisfactory due to poor personal and environmental hygiene. Hence, efforts should be made to enhance regular cleaning and monitoring of the cafeteria by the staff and owners, especially on good personal hygiene practices and appropriate hand washing techniques.